2015
DOI: 10.1002/app.42100
|View full text |Cite
|
Sign up to set email alerts
|

Phase morphology, thermomechanical, and crystallization behavior of uncompatibilized and PPgMAH compatibilized polypropylene/polystyrene blends

Abstract: In this article, we discuss the phase morphology, thermal, mechanical, and crystallization properties of uncompatibilized and compatibilized polypropylene/polystyrene (PP/PS) blends. It is observed that the Young's modulus increases, but other mechanical properties such as tensile strength, flexural strength, elongation at break, and impact strength decrease by blending PS to PP. The tensile strength and Young's modulus of PP/PS blends were compared with various theoretical models. The thermal stability, melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…(a), the value of the crystallization temperature ( T c ) for pure iPP is 119.81 °C, and T c values fall around 116 °C for the iPP/PS blends, indicating that the incorporation of PS inhibits the nucleation of iPP. Different results for the influence of PS on iPP nucleation have been reported in the literature . Mucha observed that the crystallization temperature of iPP/PS blends was lower than that of pure iPP, and assumed that there was an interaction between PP and PS which inhibited the nucleation of iPP .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…(a), the value of the crystallization temperature ( T c ) for pure iPP is 119.81 °C, and T c values fall around 116 °C for the iPP/PS blends, indicating that the incorporation of PS inhibits the nucleation of iPP. Different results for the influence of PS on iPP nucleation have been reported in the literature . Mucha observed that the crystallization temperature of iPP/PS blends was lower than that of pure iPP, and assumed that there was an interaction between PP and PS which inhibited the nucleation of iPP .…”
Section: Resultsmentioning
confidence: 98%
“…Parameswaranpillai et al . further argued that, in the process of cooling crystallization, the volume shrinkage of semicrystalline iPP was more serious than that of amorphous PS, which would squeeze the PS particles and result in chain diffusion between iPP and PS at the phase interface . However, Bartczak et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mixture of PP with PLA is an immiscible blend because they are very different in polarity, therefore it is necessary to add a compatibilizer such as polypropylenegrafted maleic anhydride (PP-g-MAH) in order to increase the properties of its blend miscibility. Parameswaranpillai [9] and Xin [10], have used PP-gMAH as a compatibilizer for PP blending with natural fibers [9,10].…”
Section: Introductionmentioning
confidence: 99%